1977
DOI: 10.1111/j.1095-8649.1977.tb05714.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of glycolysis in red and white muscles of the trout (Salmo gairdneri) and mirror carp (Cyprinus carpio)

Abstract: The activities of some glycolytic and associated enzymes have been determined in the muscles of trout and carp to investigate the possibility that the discrepancies previously reported between lactate accumulation and anoxic tolerance in these two fish result from underlying differences in glycolytic potential. Steady state concentrations of certain glycolytic intermediates were also determined in freeze-clamped muscles from tankrested fish. The activities of hexokinase, phosphorylase and phosphofructokinase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…While these findings contrast with observations in other species displaying a progressive increase in CS and PDH activity with temperature (Lemieux et al, 2010;Swimmer et al, 2004), the current findings suggest an impaired capacity to reduce NAD and FAD, and hence to provide the electrons necessary to drive the ETS, ultimately impairing ATP production in the perch heart at high temperatures. It is, however, important to note that the in vitro enzymatic activities observed in the present study might not completely reflect actual metabolic flux of living tissue in vivo, but rather the overall catalytic capacity at key steps (Johnston, 1977;Suarez et al, 1997;West et al, 1993). Therefore, the relative changes and differences between populations regarding the activity of these enzymes is what is really significant, as this provides important information concerning the modulations of mitochondrial capacity in response to warming.…”
Section: Discussion Acute Effects Of Temperature On Metabolism In Thementioning
confidence: 80%
“…While these findings contrast with observations in other species displaying a progressive increase in CS and PDH activity with temperature (Lemieux et al, 2010;Swimmer et al, 2004), the current findings suggest an impaired capacity to reduce NAD and FAD, and hence to provide the electrons necessary to drive the ETS, ultimately impairing ATP production in the perch heart at high temperatures. It is, however, important to note that the in vitro enzymatic activities observed in the present study might not completely reflect actual metabolic flux of living tissue in vivo, but rather the overall catalytic capacity at key steps (Johnston, 1977;Suarez et al, 1997;West et al, 1993). Therefore, the relative changes and differences between populations regarding the activity of these enzymes is what is really significant, as this provides important information concerning the modulations of mitochondrial capacity in response to warming.…”
Section: Discussion Acute Effects Of Temperature On Metabolism In Thementioning
confidence: 80%
“…This agrees with a recent study by Butcher et al (2011) who observed elevated AST concentrations in the plasma of keepnet-confined luderick (Girella tricuspidata) although absolute concentrations of AST were considerably lower than in the present study. It is difficult to specify the affected tissue and the degree of tissue damage, due to the occurrence of these indicators in multiple tissues and differences in enzyme activity between tissues (Johnston, 1977;Morrissey et al, 2005;Moyes et al, 2006). The increase in intracellular enzymes in the bloodstream might be due to muscle tissue damage occurring from struggle during capture and handling as assumed by others (Moyes et al, 2006;Butcher et al, 2011) or it might be due to stress-induced cell damage or increased cell membrane permeability (Pearl et al, 1966;Arakawa et al, 1997;Sánchez et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…The glycolytic capabilities of teleost white muscle are amply described (e.g., Bone et al 1978;Johnston 1977Johnston , 1981 and are evident here for the trout by the high activity of PFK found in white muscle homogenates (Table 2). Indeed, the trend of decreasing PFK activities observed in this study (red muscle > white muscle > heart > brain > kidney > liver> gill) is in general agreement with what is known regarding the glycolytic capacity of these trout organs as well as the results of previous studies on tissue-specific PFK activities (Knox et al 1980).…”
Section: Fbpase and Pfk Activities In Tissues Of The Rainbow Troutmentioning
confidence: 96%
“…White muscle FBPase maximal activity was approximately 13% of the corresponding activity in liver on a per g wet weight basis. Nevertheless, the quantity of FBPase present as white muscle enzyme may be better appreciated by considering the large proportion (approximately 65%) of body mass that is white muscle in these animals (e.g., Stevens 1968;Johnston 1977). From this perspective, it is appreciated that a 100-g animal may possess 62 units of FBPase activity arising from the white musculature.…”
Section: Fbpase and Pfk Activities In Tissues Of The Rainbow Troutmentioning
confidence: 99%